2019
DOI: 10.35234/fumbd.585312
|View full text |Cite
|
Sign up to set email alerts
|

Renk Momentleri ve Destek Vektör Makineleri Kullanarak Haploid Mısır Tohumlarının Tanımlanmasında Renk Uzaylarının Sınıflandırma Performansına Etkisinin Karşılaştırılması

Abstract: Öz: Katlanmış haploid mısır ıslah tekniği gerek ıslah süresini kısaltması, gerekse %100 homozigot hatlar elde edilmesi açısından, geleneksel ıslah yöntemleri ile karşılaştırıldığında önemli avantajlar sağlar. Katlanmış haploid mısır ıslah yönteminde önemli işlerden biri melezleme sonucunda elde edilen haploid ve diploid tohumların ayrıştırılmasıdır. Günümüzde bu işlemin elle yapılıyor olması, emek ve zaman kaybının yanı sıra yüksek sınıflandırma hatalarına neden olmaktadır. Bu çalışmada, haploid mısır tohumlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this study, SVM proposed by Vapnik [27] was used as a classifier. It has been reported that the SVM classifier shows superior performance in different agricultural image classification problems [28].…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…In this study, SVM proposed by Vapnik [27] was used as a classifier. It has been reported that the SVM classifier shows superior performance in different agricultural image classification problems [28].…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…To achieve this goal, CNN have been used to automatically recognize haploid and diploid maize seeds with a transfer learning approach. Altuntaş and Kocamaz [18] have proposed a computer-based method for the identification of haploid maize seeds. Maize seed embryos have been segmented by the k-means clustering method.…”
Section: Related Studiesmentioning
confidence: 99%